Administration of Exogenous Melatonin Improves the Diurnal Rhythms of the Gut Microbiota in Mice Fed a High-Fat Diet - Jie Yin (American Society for Microbiology, 2020)
ABSTRACT Melatonin, a circadian hormone, has been reported to improve host lipid metabolism by reprogramming the gut microbiota, which also exhibits rhythmicity in a light/dark cycle. However, the effect of the administration of exogenous melatonin on the diurnal variation in the gut microbiota in mice fed a high-fat diet (HFD) is unclear. Here, we further confirmed the antiobesogenic effect of melatonin on mice fed an HFD for 2 weeks. Samples were collected every 4 h within a 24-h period, and diurnal rhythms of clock gene expression (Clock, Cry1, Cry2, Per1, and Per2) and serum lipid indexes varied with diurnal time. Notably, Clock and triglycerides (TG) showed a marked rhythm in the control in melatonin-treated mice but not in the HFD-fed mice. The rhythmicity of these parameters was similar between the control and melatonin-treated HFD-fed mice compared with that in the HFD group, indicating an improvement caused by melatonin in the diurnal clock of host metabolism in HFD-fed mice. Moreover, 16S rRNA gene sequencing showed that most microbes exhibited daily rhythmicity, and the trends were different for different groups and at different time points. We also identified several specific microbes that correlated with the circadian clock genes and serum lipid indexes, which might indicate the potential mechanism of action of melatonin in HFD-fed mice. In addition, effects of melatonin exposure during daytime or nighttime were compared, but a nonsignificant difference was noticed in response to HFD-induced lipid dysmetabolism. Interestingly, the responses of microbiota-transplanted mice to HFD feeding also varied at different transplantation times (8:00 and 16:00) and with different microbiota donors. In summary, the daily oscillations in the expression of circadian clock genes, serum lipid indexes, and the gut microbiota appeared to be driven by short-term feeding of an HFD, while administration of exogenous melatonin improved the composition and diurnal rhythmicity of some specific gut microbiota in HFD-fed mice. IMPORTANCE The gut microbiota is strongly shaped by a high-fat diet, and obese humans and animals are characterized by low gut microbial diversity and impaired gut microbiota compositions. Comprehensive data on mammalian gut metagenomes shows gut microbiota exhibit circadian rhythms, which is disturbed by a high-fat diet. On the other hand, melatonin is a natural and ubiquitous molecule showing multiple mechanisms of regulating the circadian clock and lipid metabolism, while the role of melatonin in the regulation of the diurnal patterns of gut microbial structure and function in obese animals is not yet known. This study delineates an intricate picture of melatonin-gut microbiota circadian rhythms and may provide insight for obesity intervention.